2010
DOI: 10.1007/s00125-010-1941-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations between physical fitness and HbA1c in type 2 diabetes mellitus

Abstract: Aim/hypothesis In people with type 2 diabetes, exercise improves glucose control (as reflected in HbA 1c ) and physical fitness, but it is not clear to what extent these exercise-induced improvements are correlated with one another. We hypothesised that reductions in HbA 1c would be related: (1) to increases in aerobic fitness and strength respectively in patients performing aerobic training or resistance training; and (2) to changes in strength and aerobic fitness in patients performing aerobic and resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
51
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 40 publications
3
51
4
2
Order By: Relevance
“…To the authors' knowledge, there is no evidence on the associations for BST with CRF in T2D patients, making it necessary to further investigate the plausible mechanisms that underlie these findings. CRF was not associated with all metabolic outcomes, after adjustment for total sedentary time, contradicting previous findings on the independent associations for CRF with metabolic outcomes (Larose et al, 2011; Dickie et al, 2016). Sedentary behavior accumulating pattern is a relatively new research topic and these contradicting findings in the literature reinforce the need for further experimental investigations that may help to uncover this subject.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…To the authors' knowledge, there is no evidence on the associations for BST with CRF in T2D patients, making it necessary to further investigate the plausible mechanisms that underlie these findings. CRF was not associated with all metabolic outcomes, after adjustment for total sedentary time, contradicting previous findings on the independent associations for CRF with metabolic outcomes (Larose et al, 2011; Dickie et al, 2016). Sedentary behavior accumulating pattern is a relatively new research topic and these contradicting findings in the literature reinforce the need for further experimental investigations that may help to uncover this subject.…”
Section: Discussioncontrasting
confidence: 79%
“…CRF is a reliable metric to assess the ability of the cardiovascular system to sustain prolonged physical work, and has been shown to be one the most powerful predictors of mortality and morbidity (Despres, 2016). Poor CRF is an independent risk factor for cardiovascular diseases and related mortality (Despres, 2016), and it appears to be a link between changes in CRF and glycemic control (Larose et al, 2011; Sui et al, 2012; Dickie et al, 2016). Alongside with these results, replacing 30 min of sedentary time with LIPA provided higher benefits in metabolic profile in participants with lower CRF when compared with those with normal to high CRF levels (Ekblom-Bak et al, 2016), suggesting that the associations between sedentary pursuits and metabolic outcomes may be moderated by CRF.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly interesting because it highlights the complexity of the pathophysiology of T2D. Indeed, prior work in subjects with T2D has found a relationship between aerobic exercise training–induced changes in fitness and glycemic control (31). Furthermore, we previously found that patients randomized to a training intervention that does not increase VO 2max fail to improve glycemic control compared with patients randomized to training that increases VO 2max (3).…”
Section: Discussionmentioning
confidence: 93%
“…Until now, only one study (23) has investigated the relationships between improvement in HbA 1c and changes of V O 2peak and muscle strength in these patients. In univariate analyses, this study found that HbA 1c change was associated with the increase of V O 2peak , in the aerobic and the combined training groups, and of muscular strength, in the resistance training group.…”
Section: Discussionmentioning
confidence: 99%